Predictive factors in the retrieval of endodontic instruments: the relationship between the fragment length and location - Ricardo Portigliatti; Eugenia Pilar Consoli Lizzi; Pablo Alejandro Rodríguez (Restorative Dentistry & Endodontics)
ObjectivesThis study aimed to relate the file fragment length and location in the root canal to the retrieval chances, the clinical time required and the occurrence of secondary fractures.Materials and MethodsSixty clinical cases of fractured instruments were included in this study. They were classified according to the instrument length and the location of the root canal. In each group, the success rate in the instrument retrieval, the clinical time required and the occurrence of secondary fractures were evaluated. The collected data were analyzed using the Kruskal-Wallis test on the basis of a 0.05 significance level.ResultsThe fragment length showed no significant influence on the assessed variables (p > 0.05). The root third where the instrument was located resulted in an increased clinical time, with statistically significant differences (p < 0.05). However, the procedure success rate and the occurrence of secondary fractures showed no association with these variables.ConclusionsIn accordance with the findings of this study, the fractured fragment length did not influence any of the variables assessed, but it is suggested to focus on the fragment location inside the root canal to decide the retrieval of a fractured instrument.